2011
DOI: 10.1118/1.3635220
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance of the new hybrid PET/CT Discovery-690

Abstract: Discovery-690 shows very good PET physical performance for all the standard NEMA NU-2-2007 measurements. Furthermore, the new reconstruction algorithms available for PET data (TOF and PSF) allow further improvements of the D-690 image quality performance both qualitatively and quantitatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
288
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(298 citation statements)
references
References 50 publications
9
288
1
Order By: Relevance
“…A combination of the PSF and TOF algorithm provided the best image quality among the reconstruction algorithms using either PSF or TOF (27). Both PSF and TOF greatly improved image quality: not only in the phantom study but also in the clinical study.…”
Section: Discussionmentioning
confidence: 88%
“…A combination of the PSF and TOF algorithm provided the best image quality among the reconstruction algorithms using either PSF or TOF (27). Both PSF and TOF greatly improved image quality: not only in the phantom study but also in the clinical study.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, precise preoperative nodal staging is critical for optimal treatment planning and the long-term survival of patients (19). However, despite rapid advances In studies using phantoms, TOF technique in PET/CT has been reported to show superior performance regarding small-lesion detection, signal-to-noise ratio (SNR), and contrast resolution (18,20,21). However, quantifying and transferring these improvements to the clinical setting is complex.…”
Section: Discussionmentioning
confidence: 99%
“…Although head and neck CT scanning and MR imaging are still considered the standard imaging tests for HNSCC, there has been more evidence suggesting that PET should routinely be added to improve staging of nodal or distant disease, detection of unknown primary lesions, and surveillance for recurrence (5). 18 F-FDG PET alone was reported to achieve a sensitivity of 87%-90% and a specificity of 80%-93% in nodal staging (6). The sensitivity, specificity, and accuracy of dual-modality PET/CT were reported to be 81.1%, 98.2%, and 95.0%, respectively (7).…”
mentioning
confidence: 99%
“…Most of the current approaches to tackle the problem of the reconstruction of isotope concentration distribution can be classified into two general categories, namely the analytical methods [11,12], which rely on the inversion of Radon transform, and the iterative approaches [13,14,15,16], which are mainly based on a statistical description of the physical problem. Because of the random nature of radioactive disintegration, the tomographic data are noisy and therefore it is logical to regard PET reconstruction as a statistical estimation problem.…”
Section: Introductionmentioning
confidence: 99%